Pengaruh Green Marketing, Kualitas Produk, dan Social Media Marketing Terhadap Keputusan Pembelian pada Produk Point Coffee Indomaret Fresh Dr Sutomo Pandaan - Kirani, Mutiara Sylvi; Basalamah, Muhammad Ridwan; Wahyuningtyas, Nanik (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the influence of green marketing, product quality, and social media marketing on purchasing decisions for Point Coffee Indomaret Dr Sutomo Pandaan products. The method used is quantitative, with questionnaires distributed to 100 respondents. The population in this study is buyers who have purchased Point Coffee at Indomaret Fresh Dr Sutomo Pandaan. The sampling technique used was purposive sampling, and the data was analyzed using SPSS Version 25 software. The analysis methods employed were the F-test and t-test to determine the influence of independent variables on the dependent variable. The results of the study indicate that green marketing and product quality have a significant and positive influence on purchasing decisions, while social media marketing does not have a significant influence and has a negative influence on purchasing decisions for Point Coffee products at Indomaret Fresh Dr Sutomo Pandaan. However, simultaneously, all three variables influence purchasing decisions for Point Coffee products at Indomaret Dr Sutomo Pandaan. Keywords: Green Marketing, Product Quality, Social Media Marketing, Purchasing Decisions